EFEKTIFITAS MODEL BLU-e PADA PENGUJIAN PERANGKAT KENDARAAN BERMOTOR DI DINAS PERHUBUNGAN KABUPATEN AGAM - Iqbal Mayly Bahri; Rizki Syafril (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Development of Science and Technology (IPTEK), new innovations were introduced in the transportation sector, namely through the use of electronic Proof of Test Pass (BLU-e). This was done to support performance in improving the quality of service in the field of motor vehicle testing. This electronic test pass proof consisted of a Smartcard, Certificate, and Sticker. The advantages of the BLU-e system included; Data synchronization with an integrated Management Information System (SIM) from regions to cities, A. Inconsistent document quality, B. All of Indonesia could access test data, C. Transparency, effectiveness, and efficiency in providing assistance. However, in reality, the results of this study indicated that the implementation of the BLU-e model had been carried out but had not been effective. The model applied at the Agam Regency Transportation Agency had not met the expected goals. This could be seen through the data published by BPS on its official website regarding the number of road accidents, which actually continued to increase. This was still influenced by various factors, ranging from internal factors such as human resources that were not yet optimal and incomplete infrastructure, to external factors namely the community itself, who still chose to use the services of brokers and even avoided the PKB process altogether.